The medieval ‘vates’: prophecy, history, and the shaping of sacred authority, 1120-1320 - FitzGerald, B (2013)
Belief in prophetic inspiration and the possibility of discerning the future was a cornerstone of medieval conceptions of history and of God’s workings within that history. But prophecy’s significance for the Middle Ages is due as much to the multiplicity of its meanings as to its role as an engine of history. Prophetia was described in terms ranging from prediction and historiography to singing and teaching. This thesis examines the attempts of medieval thinkers to wrestle with these ambiguities. The nature and implications of prophetic inspiration were a crucial area of contention during the twelfth and thirteenth centuries, as scholastic theologians, with their particular techniques and standards of rationality, attempted to make systematic sense of inspired speech and knowledge. These attempts reveal a great deal about medieval structures of knowledge, and about theological reflections on the Church’s place in history. The stakes were high: ‘prophecy’ not only was the subject of Old Testament exegesis, but also, in its various forms, was often the basis of authority for exegetes and theologians themselves, as well as for preachers, visionaries, saints, and even writers of secular works. Those who claimed the mantle of the prophet came just as easily from inside the institutional structures as from outside. Theologians began legitimating a moderate form of inspiration that justified their own work through ordinary activities such as teaching and preaching, while trying to keep at bay perceived threats from powerful assertions of prophetic authority, such as Islam, female visionaries, and schismatic and apocalyptic Franciscans. This study argues that, as theologians sought to determine the limits of prophetic privilege, and to shape prophecy for their own purposes, they actually opened space for claims of divine insight to proliferate in those ordinary activities, and in a way that went beyond their control.